Examine Current Trends and Emerging Methodologies In Risk Management Practices Within Financial Markets - Rahman, Abdul; Sari, Ratna (Magister Manajemen Universitas Yapis Papua, 2023)
This study aims to examine current trends and emerging methodologies in risk management practices within financial markets. The study uses a thorough research design that includes quantitative data analysis and a review of existing literature to find essential trends in using quantitative risk assessment models, following the rules, and new technologies. Findings reveal a substantial increase in the use of Value-at-risk (VaR) and Conditional Value-at-Risk (CVaR) models, reflecting a shift towards data-driven and analytical approaches in risk management. Additionally, financial institutions are enhancing their risk governance frameworks to meet evolving regulatory requirements, highlighting the critical role of compliance in mitigating risks. Technological advancements such as artificial intelligence (AI) and blockchain are reshaping risk management practices by improving accuracy, transparency, and operational efficiency. The discussion underscores the alignment of these findings with fundamental risk management concepts and the necessity for market participants to adapt to dynamic market conditions, regulatory landscapes, and technological progress. The implications of this study suggest that embracing quantitative models, rigorous compliance measures, and technological innovations are essential strategies for effective risk management, enabling financial institutions to navigate uncertainties, mitigate risks, and seize growth opportunities in an increasingly complex financial environment.